Utilization of Digital Technology to Improve the Effectiveness of Indonesian Language Learning in Elementary Schools - Melia, Mecia; Siska Yeni Adam; Arlis Wandi; Ahmad Sabandi; Irsyad (Journal of Practice Learning and Educational Development, 2025)
The development of technology opens up great opportunities to improve the quality of learning in elementary schools, especially in learning Indonesian. This study uses a qualitative approach with a literature review method to examine the application of digital creativity in learning media. Various sources such as journals, articles, and research reports are analyzed to identify effective technologies to use, such as interactive videos, augmented reality (AR), virtual reality (VR), gamification, online learning communities, and artificial intelligence (AI)-based applications. These technologies are able to increase student motivation, engagement, and understanding interactively and personally. In conclusion, the use of digital technology in learning Indonesian in elementary schools can create a more interesting and effective learning atmosphere